Adequacyscrutinyof Intrusion Detection Techniques Over Discrete Dataset’s - Singh, Neha; Deepali Virmani, Dr. (International Journal of Engineering and Technology, 2018)
Intrusion detection is one of the major issues in wireless sensor networks. There is a drastic change in algorithms dealing with intrusion detections due to rapid change in types of intrusion. The paper presents a scrutiny of various intrusion detection techniques over various datasets and illustrates how these algorithms have evolved with time. The scrutiny is based on various parameters such as various types of technologies used to propose new systems and number of publications over a period of time, accuracy of intrusion detection rate of various data sets. The analysis concludes that their is a significant increase in new intrusion detection systems over time. The analysis also concludes that researchers are gradually shifting from old data sets to new data set to validate their systems. There is a rapid growth in systems using machine learning for intrusion detection systems.Â